Case report: Diagnostic and therapeutic challenges of fungal endocarditis by Trichosporon asahii in a child with congenital heart defects - Baptistella, Amanda; Rossato, Ana Júlia A.; de Gusmão, Beatriz C.; Cunha, Carolina M.; Trafane, Luiza F.; Colbachini, Paulo C. M. (Frontiers in Pediatrics, 2023)
Background patients with congenital cardiopathies are the main group at risk for infective endocarditis (IE) in the pediatric population. Fungal etiology is responsible for 2%–4% of all IEs, and the Trichosporon genus is an increasingly prevalent cause of infections in human beings. Case presentation We describe a 9-year-old male with multiple surgical procedures to correct congenital cardiopathy defects, including insertion of RV-PA conduit, who was admitted due to suspicion of pneumonia and needed a surgical approach after being diagnosed with a mycotic pseudoaneurysm in the right ventricle’s outflow tract, with dilation of the RV-PA conduit. The conduit was removed and antifungal treatment was started with Voriconazole after the agent was identified (T. asahii), with satisfactory therapeutic response. Approximately 4 years later, the patient was readmitted, presenting with intermittent fever, associated with nocturnal diaphoresis, dry cough, anxiety and chest pain. Vegetations consistent with T. asahii were evidenced in the RV-PA conduit, and a surgical approach was once again necessary. Discussion diagnostic methods and treatment of T. asahii endocarditis aren't yet standardized, and recurrent surgical approaches are needed due to the inefficacy of antifungal treatment.